Sustainable development of an international maritime centre - Lim, Rachel Jia Yu. (2012)
Globalization further intensified the demand for international sea transportation through increasing demand for differentiated goods from around the world, in the search of the lowest transportation costs to get these goods to their final destination with maximum efficiency. Conglomeration of various shipping-related activities within a maritime nation gradually develops it into an international maritime centre (IMC). The development journey into an IMC requires worldwide recognition and accumulation of industrial activities throughout the years. However, the most challenging part of being an IMC is its sustainable development. Only by sustaining its development can the IMC continue to maintain its competitiveness and global industrial position.